Instructional Strategies and Learning Styles as Predictors of High School students’ Academic Performance in Physics Practicals in Kenya (Proceedings of the International Conference on Future of Education, 2019)
The desire of every teacher and every educator is to improve academic performance in schools and colleges. Meaningful teaching and learning  requires flexibility, creativity and responsibility in order to provide a conducive learning environment  able to respond to the learner’s individual needs.  A host of research has been conducted to investigate various factors that influence academic performance. Among such factors is the preferred learning styles of learners. A quasi – experimental pre-test post–test non-equivalent control group design was conducted to investigate how three learning styles (visual, auditory and kinaesthetic) and three teachers' instructional strategies (guided-inquiry, cooperative learning and direct instruction) predict academic performance (achievement test scores and acquisition of science process skills) in Physics practical work while controlling for gender. A sample of five hundred and nineteen (519) form three physics students were selected through multistage sampling procedures (purposive sampling, proportionate stratified random sampling and simple random sampling). Physics Achievement Tests 1 and 2 (PAT1 & PAT2), Learning Style Questionnaire and Physics Process Skills Checklist (PPSC).Teachers’ Instructional Guides on Guided-Inquiry (TIGITS), Cooperative(TIGCTS) and Direct Instructional Strategy(TIGDITS) were used to collect quantitative data.. Validity and reliability of the instruments were assessed. Data were analysed using multiple Linear Regression test. Results indicated that while Teachers’ Instructional Strategies contributed significantly to the model (B= 3.266, p
Keywords: Instructional practices; learning styles; performance